Penerapan Vouching Dan Tracing Di Era Remote Audit: Integrasi Solusi Digital Untuk Meningkatkan Keabsahan Transaksi Klien Kap XYZ - Muzakki, Imam Mahmud; Kirana, Nanda Wahyu Indah (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2026)
Digital transformation and pressure for cost efficiency are driving fundamental changes in audit practices, especially in vouching and tracing procedures that are now performed remotely. This research aims to examine how the integration of digital solutions can improve transaction validity, reduce operational costs, and minimize miscommunication between auditors and clients. Using a descriptive qualitative approach through direct observation and document analysis at XYZ Public Accounting Firm, it was found that remote auditing raises the risk of document invalidity due to limited physical access, digital data fragmentation, and weak evidence authentication systems. However, these challenges can be overcome through the implementation of an integrated audit trail system and the use of digital platforms that support continuous communication between auditors and clients. These findings confirm the importance of strengthening digital infrastructure in modern audit practices to maintain the credibility, effectiveness, and accountability of auditors' work in the era of remote auditing.